2022
DOI: 10.1155/2022/4300840
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Particle Swarm Algorithm in Nanoscale Damage Detection and Identification of Steel Structure

Abstract: In order to identify the damage of a grid structure, the author proposes a damage identification method for grid structures based on particle swarm optimization. First, using the Modal Assurance Criterion (MAC) and combining the respective advantages of frequency and mode shape in damage identification, a fitness function based on frequency and mode shape is constructed. Second, two test functions are used to compare and analyze, which shows that the improved particle swarm algorithm has better optimization pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…(4) Optimization of particle swarm optimization variables. Particle swarm optimization algorithm is a novel optimization algorithm with fast convergence speed, high accuracy, and easy to find the global optimal solution (Zhang, 2022), which is very suitable as an optimization algorithm for this method.Fig. 4 plots the flow chart of the algorithm.…”
Section: Solving and Optimization Of Particle Swarm Optimizationmentioning
confidence: 99%
“…(4) Optimization of particle swarm optimization variables. Particle swarm optimization algorithm is a novel optimization algorithm with fast convergence speed, high accuracy, and easy to find the global optimal solution (Zhang, 2022), which is very suitable as an optimization algorithm for this method.Fig. 4 plots the flow chart of the algorithm.…”
Section: Solving and Optimization Of Particle Swarm Optimizationmentioning
confidence: 99%
“…The particle swarm optimization (PSO) is a swarm intelligence optimization algorithm, introduced by Kennedy and Eberhart in 1995. The basic principle is to mimic the behavior of a group of birds (particle swarm) in a forest (search space) seeking food based on the quantity of food (fitness value), to find the location with the most food (group best position) [46]. Each particle in the swarm is characterized by three attributes: position, velocity, and fitness value.…”
Section: Parameter Optimization Based On Particle Swarm Optimizationmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%